Integration of Project based Learning Model in Music Art Learning in Higher Education (International Journal of Educational Technology Research, 2024)
This research was conducted to minimize student inactivity in the process of learning music arts. Project-based learning is one approach that can affect the learning process of musical arts. This study used a literature review by analyzing the results of reviews from national journals.  The results showed that there was a change in student activity in class in learning music arts. This can be seen from the increase in student involvement in the music learning process and the increase in student activity increased from giving projects to students through the process of planning, implementation, observation and evaluation stages.
Keywords: Project , Based, Learning